Gender-just mitigation in the agrifood systems sector: Potential and pitfalls - Nassif, Gabriella; Ringler, Claudia; Bryan, Elizabeth (Annual Reviews, 2025)
Mitigation action in agrifood systems is essential for addressing growing negative impacts from climate change. It remains unclear, however, to what extent mitigation in the agrifood systems space addresses gender inequalities and involves women as agents of climate action. This article reviews the literature to identify the main linkages between gender and mitigation in agrifood systems, examines the key barriers preventing women from equitably participating in and benefiting from mitigation actions in agrifood systems, and concludes with best practices to mainstream gender in mitigation actions in a substantive and sustainable way. Promising approaches include strengthening women's land rights; supporting women's economic empowerment through access to finance, information, and opportunities; and supporting women's groups.